2009
DOI: 10.1001/archfacial.2009.10
|View full text |Cite
|
Sign up to set email alerts
|

Thread-lift for Facial Rejuvenation

Abstract: The thread-lift provides only limited short-term improvement that may be largely attributed to postprocedural edema and inflammation. Our results objectively demonstrate the poor long-term sustainability of the thread-lift procedure. Given these findings, as well as the measurable risk of adverse events and patient discomfort, we cannot justify further use of this procedure for facial rejuvenation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
29
0
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 91 publications
(30 citation statements)
references
References 11 publications
0
29
0
1
Order By: Relevance
“…Lycka et al 33 showed only one-third of patients maintaining 70% of their original effect 1–2 years after surgery. A controlled case series by Abraham et al 32 showed minimal improvement on blinded assessment when compared to a control group who had undergone other rejuvenation procedures.…”
Section: Minimally Invasive and Noninvasive Techniquesmentioning
confidence: 99%
See 1 more Smart Citation
“…Lycka et al 33 showed only one-third of patients maintaining 70% of their original effect 1–2 years after surgery. A controlled case series by Abraham et al 32 showed minimal improvement on blinded assessment when compared to a control group who had undergone other rejuvenation procedures.…”
Section: Minimally Invasive and Noninvasive Techniquesmentioning
confidence: 99%
“…This technique involved subcutaneous placement of barbed threads, which were pulled to achieve the lift and trimmed at the entry point. 32 The marketed advantage was that it was a “non-surgical” technique with minimal convalescence and instant results. However, several studies have brought into question the peak effect and longevity of the procedure.…”
Section: Minimally Invasive and Noninvasive Techniquesmentioning
confidence: 99%
“…Furthermore they asserted that the examined thread lifts relied on a similar basic technique involving subcutaneous placement of cogged threads along a planned trajectory, the threads being pulled to achieve the desired skin lift, secured and trimmed at the entry point. [2] However such studies do not apply to certain well sustained and successful percutaneous thread lift techniques. Technique integrity necessitates methods that must be ingenious in anatomical design, providing for acceptable long term tissue suspension outcomes without significant side effects and risks.…”
Section: Historymentioning
confidence: 99%
“…Recently introduced the quick-recovery and small-incision face lifting, micro-focused ultrasound with high-resolution ultrasound visualization (MFU-V), and internal suture suspension that can surmount obvious obstacles of traditional surgical facelift [11]. The common advantages of this type of less-invasive plastic surgery include fast operation time, no general anesthesia, short recovery time, and fewer complications, which brings a lot of convenience to patients and surgeons [12]. However, it is worth noting that the use of fillers may cause stiff countenance and unnatural contours after the face is filled.…”
Section: Introductionmentioning
confidence: 99%